KAJIAN SEMIOTIK BUDAYA MASYARAKAT: Nilai Keislaman dalam Tradisi Ter-ater di Lumajang (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2020)
This article examines the Islamic values ​​embodied in the “ter-ater” tradition in Lumajang. “Ter-ater” is a habit of the people in Lumajang, at certain moments, distributing food to neighbors or relatives in the surrounding environment. Before food is distributed, the people pray tohether first. The method used in this study is qualitative with a semiotics approach. The research location is Kalipenggung Village, Randuagung District, Lumajang Regency. Data collection techniques are interviewing, observing, and studying literature. Data analysis are performed by reducing or sorting, presenting, and formulating conclusions. The results of this study state that there are Islamic values ​​in the “ter-ater” tradition, among others, to foster a spirit of charity, strengthen brotherhood among Muslims, and preserve good habits in the community. This research is useful as an addition to the scientific literature in the field of communication, especially the science of semiotics, in connection with the study of the traditions of the Islamic community.